De la bande dessinée aux bandes écoutées - Laurent Bozard (Comicalités)
The Blynd application has been offering the audio adaptation of successful comics in episodes and series since 2020. This study first analyzes the editorial positioning of the company (between cinema, sound and comics). Second theme: the “numerimorphosis” of the device and the changes (paper/digital/sound) that it inflicts on the contents in order to arrange them in another form of serialization. Through a series of commented examples, the analysis focuses on the division into chapters/episodes and its narratological scope. Finally, the study aims to determinate the changes that this type of adaptation causes on the stories offered to the listener, with the help of extracts and an interview with a scriptwriter.